(untitled) (Journal of the College of Basic Education, 2025)
Based on the exploratory study conducted by the researchers on the artistic skills acquired by second-year students - Department of Art Education - College of Fine Arts in the sculpture subject prescribed in their curricula and how to employ them in completing contemporary sculptural works, it therefore appeared to them that the research community lacks information in the field of contemporary sculpture. The most important artistic works accomplished by artists in this specialty. Based on the above, the two researchers decided to establish the problem of the current research by employing metal waste in the sculptural works of art education students. The research population consisted of students in the second year - Department of Art Education, who numbered (82) male and female students. A random sample of (13) male and female students was selected. To achieve the goal, (11) teaching plans, a cognitive achievement test, and a skill performance evaluation form were designed, which were presented to A group of experts to verify its validity in measuring the research objective, to show the results of the research, the researchers relied on the Wilcoxon equation, the Keuder-Richardson/20 equation, and the Cooper equation. The most important conclusions are: The diversity of educational experiences and the methods of presenting them in the content of teaching plans can attract the student’s attention as they are among the basics of successful teaching and help him learn information and acquire technical skills. The most important recommendations are: Paying attention to the cognitive aspect in teaching the subject of sculpture and linking it to the skill aspect, sequentially, in the information related to skills to improve them for art education students in employing various metal wastes to fulfill the requirements of this subject for contemporary works of art.